CONTRIBUTION OF PEASANT MIGRATION TO HOUSEHOLD FOOD SECURITY: A CASE STUDY OF KIDEA VILLAGE OF KIGOMA RURAL DISTRICT, TANZANIA - Juma Tegeje (European Scientific Journal, ESJ, 2014)
There is limited information about the contribution of peasant migration to household food security in Tanzania because many studies conducted in the country have put less emphasis on this aspect. This study assessed the contribution of peasant migration to household food security using Kidea Village of Kigoma Rural District. Land ownership status; types of crops grown; food availability and access; post-harvest food management practices; the amount of food harvested and length of time it lasted were used as determinants of food security. Household questionnaire, focus group discussion, physical observation and key informant interviews were used in data collection. The findings show that all respondents had security of land tenure. This enabled more food production. Investment in multiple cropping helped to accommodate risks and uncertainties from unforeseen poor climatic conditions. The reported post-harvest food management practices including food donations and brewing did not contribute to food insecurity since their frequencies and amounts were occasional and small, respectively. A high proportion of respondents reporting adequate and affordable food in the village market imply that exchange between food-surplus and fooddeficit households was made possible. In addition, majority of respondents reporting better production of crops at destination than in their places of origin and which lasted to the next harvest imply that households were food secure. However, it was noted that migration to Kidea is more of subsistence than long term investment in economic development.